Adversities identified by nurses in the depletion of access for dialysis therapies1 (Research, Society and Development, 2022)
The objective that guided the research was to know the difficulties identified by nurses in the exhaustion of access to dialysis therapies. Method: this is a descriptive study, with a qualitative approach, in which 12 care nurses participated in day, night and day shifts and approved by Plataforma Brasil under the opinion number 4,406,281. Data collection was guided by the semi-structured interview technique. Data analysis was performed based on an emerging category from the revealed content, using Bardin's content analysis technique. Results: research data revealed that nephrologist nurses identify difficulties in the exhaustion of access to dialysis therapies as well as stress to chronic kidney patients. Conclusion: considering that the study was carried out focusing on nurses working in the nephrology sector, it is considered important to develop new studies for the dissemination of knowledge for good practices in care for access to renal replacement therapies.